Unequal Treatment of Identical Agents in Cournot Equilibrium - Salant, Stephen W; Shaffer, Greg (American Economic Review, 1999)
Oligopoly models where prior actions by firms affect subsequent marginal costs have been useful in illuminating policy debates in areas such as antitrust regulation, environmental protection, and international competition. We discuss properties of such models when a Cournot equilibrium occurs at the second stage. Aggregate production costs strictly decline with no change in gross revenue or gross consumer surplus if the prior actions strictly increase the variance of marginal costs without changing the marginal-cost sum. Therefore, unless the cost of inducing second-stage asymmetry more than offsets this reduction in production costs, the private and social optima are asymmetric. (JEL D43, L13, L40)